Liquid-phase intermediated chemical vapor deposition for ternary compositional 1D van der Waals material Nb2Pd3Se8 - Lee, Sang Hoon; Jeong, Byung Joo; Choi, Kyung Hwan; Jeon, Jiho; Lee, Bom; Cho, Sooheon; Kim, Dahoon; Gudena, Gutema Teshome; Megersa, Daba Deme; Kim, Sang Hyuk; Yu, Hak Ki; Choi, Jae Young (CrystEngComm, 2024)
In the case of low-dimensional semiconductor devices, the basic physical properties of materials can be measured through device manufacturing using single crystal synthesis and exfoliation, but for expansion into various application fields, technology that can synthesize the material itself directly on the substrate is needed. For multi-composition low-dimensional semiconductor materials like Nb2Pd3Se8, the physical characteristics of constituent elements differ, making direct growth control on a substrate extremely challenging. This study successfully synthesized Nb2Pd3Se8 wires using different metal precursors (niobium and palladium) through liquid precursor-intermediated chemical vapor deposition (LPI-CVD). By adjusting the concentration of the liquid precursor and the synthesis temperature, the reproducible growth of Nb2Pd3Se8 wires was achieved, ranging in lengths from 2.29 to 15.04 μm. It was confirmed that PdSe2 is initially synthesized at lower temperatures (below 620 °C), and at temperatures above 620 °C, this PdSe2 transforms into Pd17Se15. Nb2Pd3Se8 is synthesized from the Pd17Se15 at these higher temperatures. X-ray diffraction (XRD) analysis revealed that the wires exhibit a preferred orientation along the (210) plane. Electronic device fabrication using these wires demonstrated their application potential as n-type semiconductors. Field-effect transistor (FET) measurements revealed remarkable performance, with an Ion/Ioff ratio of 575 and an electron mobility of 2.03 cm2 V−1 s−1. LPI-CVD provides a promising strategy for synthesizing ternary chalcogenide materials, opening possibilities for exploring diverse ternary phases. This study highlights the importance of controllability, reproducibility, and FET performance in growing Nb2Pd3Se8 wires via the CVD system, thereby paving the way for integrated applications and facilitating mixed-dimensional studies with other nanomaterials.
Keywords: Chemical vapour deposition; Crystal synthesis; Field-effect transistor; Liquid Phase; Liquid phasis; Liquid precursors; Low-Dimensional Semiconductors; Physical properties of materials; Synthesised; Van der Waal